Impact of Societal and Economic Development on Academic Performance: A Literature Review - Hayat, Khunsa; Yaqub, Kamran; Aslam, Muhammad Ali; Shabbir, Malik Shahzad (iRASD Journal of Economics, 2022)
The impact of societal and economic development on academic performance is a circle that needs to be established by the developing economies. This research aims to identify the factors that are associated with increased academic performance in Pakistan which is found to be challenging. This study collected secondary qualitative data from 30 research studies published in global and international journals which helped in investigating the role of societal and economic development on academic performance. It is suggested that the country invests in its educational sector and provide an improved outlook to the economy and aid the society which will, in turn, benefit the academic performance of the whole country. Therefore, it is concluded that societal and economic development play an important role in determining academic performance.